KEWENANGAN PEMERINTAH DAERAH DALAM PENYELENGGARAAN INVESTASI DAERAH - Rudy Catur Rohman Kusmayadi (LP3M IAI Al-Qolam Malang, 2015)
This writing aims at describing the matters concerning the change of the orientation and implementation of local development that is based on the principle of the widest, real and responsible otonomy delegation and also on the law number 32-2004 about local development an the law number 33-2004 about the financial balance between territorial and central government. The aspect of financial balance is made to create fair and wide spread development as well as to get the sufficient financial source in the frame work of eliminating the bad impact of territorial wisdom in increasing PAD (territorial income) throughextencification of taxation. Therefore, territorial government paradigm producing entrepreneurship financial source must initially be developed. This is in line with the soul of territorial otonomy stating that the territorial government can carry out financial capital participation in both government and private territorial enterprise. The replacement of government orientation in the meet of territorial needs based on the territorial potency itself is expected to be aisle to shuffle all kind of challenges in carrying out the govermential duty through the intervention of more accurate territorial policy or wisdom. It is expected that the participation, initiative and creativity of society in business sector and social institution can be increased to endeavoar people or society. Keywords : Authorities, Autonomous Regions, Regional Investment